Triggering multi-actor change cascades: Non-representational theory and deep disaster risk management co-production. (December 2020) - Hope, Max; McCloskey, John; Nicbhloscaidh, Mairead; Crowley, Dominic; Hunt, Dom
Deep-rooted socio-ecological and technical systems, values and lifestyles, 'locked in' by vested interests and flows of power, underpin the interconnected problems of climate change, hazard vulnerability and poverty. A 'shallow' approach to co-production, with its focus on knowledge exchange and shared learning between individuals, struggles to gain the 'purchase' needed to transform these material structures. In this paper we demonstrate that non-representational theory is a good starting point for an alternative 'deep' approach to disaster risk management co-production. We review key aspects of non-representational theory and their application to disaster risk management and build a novel hybrid conceptual framework. We use this to analyse a case study of disaster risk management co-production (an aftershock forecasting approach used by humanitarian agencies during the Nepal 2015 earthquake), how social change occurred in this instance, and the role disaster risk management co-production played. We emphasise how change was the consequence of unexpected shifts in assemblages of human, non-human, virtual and real actors. These created 'events' that were opportunities for change that were realised with fidelity. Using this analysis, we develop an alternative deep approach to co-production, as 'a practical means of going on', and finish with five precepts to guide transformative disaster risk management based on the concept of multi-actor change cascades.